Laboratory Test Methods to Determine the Degradation of Plastics in Marine Environmental Conditions - Tosin, Maurizio; Weber, Miriam; Siotto, Michela; Lott, Christian; Degli-Innocenti, Francesco (Frontiers in Microbiology, 2012)
In this technology report, three test methods were developed to characterize the degradation of plastic in marine environment. The aim was to outline a test methodology to measure the physical and biological degradation in different habitats where plastic waste can deposit when littered in the sea. Previously, research has focused mainly on the conditions encountered by plastic items when floating in the sea water (pelagic domain). However, this is just one of the possible habitats that plastic waste can be exposed to. Waves and tides tend to wash up plastic waste on the shoreline, which is also a relevant habitat to be studied. Therefore, the degradation of plastic items buried under sand kept wet with sea water has been followed by verifying the disintegration (visual disappearing) as a simulation of the tidal zone. Most biodegradable plastics have higher densities than water and also as a consequence of fouling, they tend to sink and lay on the sea floor. Therefore, the fate of plastic items lying on the sediment has been followed by monitoring the oxygen consumption (biodegradation). Also the effect of a prolonged exposure to the sea water, to simulate the pelagic domain, has been tested by measuring the decay of mechanical properties. The test material (Mater-Bi) was shown to degrade (total disintegration achieved in less than 9 months) when buried in wet sand (simulation test of the tidal zone), to lose mechanical properties but still maintain integrity (tensile strength at break = -66% in 2 years) when exposed to sea water in an aquarium (simulation of pelagic domain), and substantially biodegrade (69% in 236 days; biodegradation relative to paper: 88% ) when located at the sediment/sea water interface (simulation of benthic domain). This study is not conclusive as the methodological approach must be completed by also determining degradation occurring in the supralittoral zone, on the deep sea floor, and in the anoxic sediment.